100 Years of Chronogeometrodynamics: The Status of the Einstein's Theory of Gravitation in Its Centennial Year - Elias C. Vagenas (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
In 1692, Newton wrote: "That gravity should be innate, inherent and essential to matter so that one body may act upon another at a distance through a vacuum, without the mediation of anything else by and through which their action or force may be conveyed from one to another, is to me so great an absurdity that I believe no man who has in philosophical matters any competent faculty of thinking can ever fall into it. Gravity must be caused by an agent acting constantly according to certain laws, but whether this agent be material or immaterial is a question I have left to the consideration of my readers". One of them who, just over 200 years later, picked up the baton of Newton was Albert Einstein. His General Theory of Relativity, which had its centenary in 2015, opened up new windows on our comprehension of Nature, disclosed new, previously unpredictable, phenomena occurring when relative velocities dramatically change in intense gravitational fields reaching values close to the speed of light and, for the first time after millennia of speculations, put Cosmology on the firm grounds of empirically testable science. This Special Issue was dedicated to this grand achievement of the human thought.